2006
DOI: 10.1152/ajpheart.01348.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple coherence of cerebral blood flow velocity in humans

Abstract: The coherence function has been used in transfer function analysis of dynamic cerebral autoregulation to assess the statistical significance of spectral estimates of gain and phase frequency response. Interpretation of the coherence function and choice of confidence limits has not taken into account the intrinsic nonlinearity represented by changes in cerebrovascular resistance due to vasomotor activity. For small spontaneous changes in arterial blood pressure (ABP), the relationship between ABP and cerebral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 43 publications
(78 reference statements)
6
78
0
Order By: Relevance
“…This is not surprising because, unlike traditional approaches, the MMPF makes no assumptions of stationary signals and linear BP-BFV relationships and, thus, can more reliably quantify nonlinear relationship between nonstationary signals such as blood pressure and blood flow velocity. This result along with other findings indicate that inherent nonlinearities of cerebral autoregulation can be better described by nonlinear methods such as MMPF and multivariate coherence-an approach that takes into account contributions of other inputs, e.g., pressure and cerebrovascular resistances (Panerai et al 2006). Note that, for a demonstration that MMPF can be used for the assessment of autoregulation during baseline conditions, we applied the method to one selected cycle of spontaneous BP and BFV oscillations during baseline each time.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is not surprising because, unlike traditional approaches, the MMPF makes no assumptions of stationary signals and linear BP-BFV relationships and, thus, can more reliably quantify nonlinear relationship between nonstationary signals such as blood pressure and blood flow velocity. This result along with other findings indicate that inherent nonlinearities of cerebral autoregulation can be better described by nonlinear methods such as MMPF and multivariate coherence-an approach that takes into account contributions of other inputs, e.g., pressure and cerebrovascular resistances (Panerai et al 2006). Note that, for a demonstration that MMPF can be used for the assessment of autoregulation during baseline conditions, we applied the method to one selected cycle of spontaneous BP and BFV oscillations during baseline each time.…”
Section: Discussionmentioning
confidence: 72%
“…CPP is calculated from intra-arterial (ABP) and intracracranial pressure (ICP) recordings (i.e., CPP = ABP−ICP). The MMPF, as well as other autoregulation analyses (Diehl et al 1995;Tiecks et al 1995;Panerai et al 2006), quantified the BP-BFV relationship based on peripheral arterial blood pressure (ABP) due to the complicated and invasive experimental settings for ICP measurements. Though in normal condition the change in CPP is dominated by the change in ABP and many studies indicated that the ABP-BFV relationship can be used to identify the alteration and impairment in autoregulation, it is important to understand whether there is a difference between the autoregulation measures based on ABP and CPP.…”
mentioning
confidence: 99%
“…Therefore, a single transfer function may be not sensitive enough to identify the influences of cerebral autoregulation at different time scales and to assess nonlinearities in pressure-flow relationship using a small sample size of subjects. Furthermore, another intrinsic problem of the transfer function is that low values of univariate coherences between two signals (e.g., coherence <0.5 for BP-BFV transfer function at frequency <0.07Hz) violate the assumption of a linear relationship between two signals and thus may preclude use of gain and phase as measures of coupling strength between BFV and BP [57].…”
Section: B Active Frequency Range Of Cerebral Autoregulationmentioning
confidence: 99%
“…These findings provide additional important evidence to support that cerebral autoregulation is a continuous dynamic process, influencing BP-BFV relationship at multiple time-scales over a larger frequency range. They also suggest that inherent nonlinearities of cerebral autoregulation can be better described by nonlinear methods such as MMPF [17,48,51], multivariate coherence [57], and general Volterra-Wiener approaches [56,58,59].…”
Section: B Active Frequency Range Of Cerebral Autoregulationmentioning
confidence: 99%
“…4 -6 In contrast to static autoregulation, which describes CBF responses to steady-state changes in BP, dynamic autoregulation examines CBF responses to transient changes in BP in time scales of seconds to minutes, which may be critical in preserving CBF during rapid perturbations in BP presented in daily life. 4,6 Recently, several studies have shown that dynamic autoregulation is likely to be preserved in patients with mild to moderate hypertension 5,7,8 but becomes less effective in severe hypertension. 9 However, one important question yet to be answered is whether dynamic autoregulation is altered at the initial stages of lowering of BP consequent to effective antihypertensive treatment.…”
mentioning
confidence: 99%